Determination and comparison of phospholipid profiles in eggs from seven different species using UHPLC-ESI-Triple TOF-MS - Zhou, Li; Yang, Fu; Zhao, Minjie; Zhang, Minghao; Liu, Jikai; Marchioni, Eric (Food chemistry, 2021)
[Display omitted] •Phospholipid molecular species of seven egg types were characterized and quantified.•Chemometrics was used to screen the differential markers for various eggs.•Eighty-seven molecular species were identified by UHPLC-ESI-Triple TOF-MS.•Phospholipid profiles of pigeon and hen eggs were significant different from other eggs. Egg yolk phospholipids from seven different species were purified (purity > 96%) using SPE columns, and subsequently the phospholipid profiles were identified and quantified by ultra-high-performance liquid chromatography-electrospray ionization-triple time-of flight mass spectrometry (UHPLC-ESI-Triple TOF-MS). Eight phospholipid classes and 87 molecular species were characterized. Principal component analysis showed that the molecular species and concentration of phospholipids in pigeon and hen egg yolks had a significant difference with other eggs. Hierarchical cluster analysis indicated that the phospholipid profiles of pigeon egg yolks were closest to hen egg yolks, followed by quail, duck, ostrich, emu and goose egg yolks. Different relative quantities of certain molecular species were different among egg yolk types; for instance, phosphatidylcholine (16:0/16:1) in goose egg yolks and phosphatidylethanolamine (16:0/18:3) in ostrich egg yolks. This study provides a basis for a better understanding of the phospholipid profiles of egg yolks, and better evaluation of the nutritional value of eggs.